La différenciation pédagogique du point de vue d’enseignants québécois : quelles différences pour les pratiques d’enseignement en contexte d’entrée dans l’écrit? - Nootens, Pascale; Morin, Marie-France; Montesinos-Gelet, Isabelle (Canadian Journal of Education/Revue canadienne de l’éducation, 2012)
Adapting teaching to the needs of students and their skill level is now acknowledged as a key ingredient to their success at school. However, little progress appears to have been made in regular classes in accompanying students with differing needs (McLeskey & Waldron, 2002). Our study seeks to describe declared differentiated teaching practices implemented at the beginning of writing learning by 20 teachers viewed as exemplary in this regard. Globally, our study results show that practices involve for the most part adapting the support offered to students and adapting teaching strategies and methods to student characteristics. However, the teachers we questioned appear to lack references with regard to the formal evaluation of acquired competencies. Keywords : Differentiation, evidence-based practices, literacy, primary grade.